Hadis Dalam Perspektif Sejarah Sosial dan Hukum Islam - Heryani; M. Hasbi Umar; Ramlah (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This research examines Hadith as the second source of Islamic legal teachings from the Qur'an. The study of Hadith as a source of Islamic law has attracted the attention of enthusiasts of Hadith studies, not only from Muslims, but also from non-Muslims, even to this day the study of Hadith issues, whether in the form of criticism of its authenticity or methods of understanding, continues to develop both textually. as well as contextually. This research uses a qualitative descriptive method and is a type of library research.This study found that there were differences among scholars in defining hadith. In history, only a small group of Muslims have rejected hadith as a source of Islamic teachings. They are known as inkarus-sunnah. However, what has become a problem among many Muslims is the criteria for a hadith to become evidence, the scholars have divided hadith based on its quality which is divided into three categories, namely authentic hadith, hasan hadith, and daif hadith. Finally, as forthe function of the Hadith to the Qur'an is as Bayan At-Taqrir (Clarifying the Contents of the Al-Quran), Bayan At-Tafsir (Interpreting the Contents of the Koran), Bayan At-Tasyri (Giving Certainty to Islamic Law That Is Not in the Al-Quran), and Bayan Nasakh (Replacing the Previous Provisions).